2012
DOI: 10.1186/2041-9139-3-22
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and evolutionary divergence in the activity of receptor-regulated smads

Abstract: BackgroundActivity of the Transforming growth factor-β (TGFβ) pathway is essential to the establishment of body axes and tissue differentiation in bilaterians. Orthologs for core pathway members have been found in all metazoans, but uncertain homology of the body axes and tissues patterned by these signals raises questions about the activities of these molecules across the metazoan tree. We focus on the principal canonical transduction proteins (R-Smads) of the TGFβ pathway, which instruct both axial patternin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The BMP arm of the TGF-b signalling is asymmetrically expressed along the directive axis (orthogonal to the anterior/posterior axis) of the sea anemone Nematostella vectensis [38,53,54] and has been implicated in defining the bilateral axis of symmetry in cnidarians [39,43]. Furthermore, ectopic expression of NvSMAD (a SMAD homologue isolated from Nematostella vectensis) in Xenopus during development has demonstrated that the Nv homologue of this gene is sufficient to recapitulate the ventralized phenotype generated by vertebrate homologues in similar studies [40]. Similarly, using in situ hybridization, Adamska et al [30] identified asymmetrical expression of TGF-b along the larval swimming axis in sponge embryos and Pang et al [31] revealed that TGF-b …”
Section: Pathways That Unite Metazoans (A) Transforming Growth Factormentioning
confidence: 99%
“…The BMP arm of the TGF-b signalling is asymmetrically expressed along the directive axis (orthogonal to the anterior/posterior axis) of the sea anemone Nematostella vectensis [38,53,54] and has been implicated in defining the bilateral axis of symmetry in cnidarians [39,43]. Furthermore, ectopic expression of NvSMAD (a SMAD homologue isolated from Nematostella vectensis) in Xenopus during development has demonstrated that the Nv homologue of this gene is sufficient to recapitulate the ventralized phenotype generated by vertebrate homologues in similar studies [40]. Similarly, using in situ hybridization, Adamska et al [30] identified asymmetrical expression of TGF-b along the larval swimming axis in sponge embryos and Pang et al [31] revealed that TGF-b …”
Section: Pathways That Unite Metazoans (A) Transforming Growth Factormentioning
confidence: 99%
“…SMAD linkers are inter-domain sequences of approximately 100–120 residues, characteristic of each type of SMAD protein [5] , [31] . There is no structural information available, except for short fragments of SMAD1, SMAD2 and SMAD7, which were studied as complexes bound to transcription activators and ubiquitin ligases [14] .…”
Section: Resultsmentioning
confidence: 99%
“…This rapid change indicates that the effects are at least partly mediated by the non‐genomic function of RARγ rather than through genomic action that would require changes in gene expression and production of new proteins, both likely requiring more than 1 h. In vitro studies showed that RARγ physically interacts with the MH2 domain of Smad3 and down‐regulates Smad3/4‐dependent transcription in the presence of RARγ agonists, while Smad3/4‐dependent transcription activity was markedly increased by RAR pan‐antagonist treatment . The MH2 domain is used for protein–protein interactions, including hetero‐trimerization of Smads, and is highly conserved especially among the R‐Smad proteins . Thus, RARγ may directly interact with Smad1/5/8 proteins and modulate their function.…”
Section: Discussionmentioning
confidence: 99%
“…29 The MH2 domain is used for protein-protein interactions, including heterotrimerization of Smads, and is highly conserved especially among the R-Smad proteins. 30 Thus, RARg may directly interact with Smad1/5/8 proteins and modulate their function. On the other hand, RARg is also known to interact with Src, a non-receptor tyrosine kinase, and ligand-bound RARg enhances Src kinase activity.…”
Section: Discussionmentioning
confidence: 99%